The Use a Prophylactic Intramedullary Tibial Nail for a Stress Fracture in a High-Level Athlete - Collins, Devin W (J Orthop Case Rep, 2020)
INTRODUCTION: Mid-diaphyseal anterior tibial stress fractures can be debilitating injuries. They have been described occurring in athletes due to repetitive lower extremity trauma. The purpose of our study was to highlight a case of an athlete sustaining a tibial stress fracture with multiple cortical defects. CASE REPORT: We present an 18-year-old collegiate bound athlete who sustained a tibial stress fracture with multiple cortical defects. The clinical decision, after failure of conservative treatment, was made to treat the patient with tibial intramedullary nailing. She was able to return to full unrestricted activities, including high-level sports participation. Our case report specifically describes a case of a high-level athlete with multiple anterior tibial linear cortical defects from a chronic stress fracture. CONCLUSION: When conservative management for mid-diaphyseal anterior stress fractures fails, the utilization of prophylactic tibial nailing is a viable option. The decision for surgical intervention is dependent on many factors including patient’s activity level and characteristics, failure of conservative management, and radiographic evidence of non-healing stress fractures.